Implications of Network Convergence on Local Access Regulation in the U.S. and the EU - Margit A. Vanberg (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2007)
This paper provides an overview of telecommunications regulation in the U.S. and in Europe. For each region the history of telecommunications regulations as well as the current regulatory regime is portrayed. The focus of this overview is on the question of how unbundling regulations in the local access market have evolved in parallel to the convergence of telecommunications with Internet and broadcasting services. The criteria used by the regulatory authorities to identify those network elements which incumbents are required to offer to competitors at regulated rates are compared to the criteria provided by the ?essential facilities doctrine?, a concept used in antitrust law. The analysis concludes that U.S. deregulation has gone too far with respect to some broadband access markets while in Europe, a severe tendency to overregulation is observed.
Keywords: L15; L43; 330; network convergence; unbundling regulation